Acute ST-Elevation Myocardial Infarction Associated with Metabolic Syndrome and Its Angiographic Outcome - Huda, Reaz Mahmud; Mozaffor, Miliva; Alam, Mohammad Ashraful; Hossain, Md Delwar (Journal of Bangladesh Society of Physiologist, 2021)
Background: Metabolic Syndrome is already one of the major public health problems around the world; it may be more grievous when associated with any cardiac emergency like myocardial infarction (MI). Objective: To evaluate the association of metabolic syndrome and its angiographic effects on patients with Acute ST-Elevation Myocardial Infarction (acute STEMI). Methods: This prospective observational study was done in the Department of Cardiology of the National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh, between July and December of 2013. A total 233 patient were selected for data collection; of them 109 were in group I (acute STEMI patients with metabolic syndrome) and 124 in group II (acute STEMI patients without metabolic syndrome). Initial evaluation of the patients was done by history taking and clinical examination. Baseline investigations like ECG, CK(MB), lipid profile, fasting blood sugar, serum creatinine and echocardiography were done. Coronary angiogram (CAG) was done in the Cardiac Cath-Lab facility of the same hospital. Data was analyzed by using SPSS version 16.0. Comparison between groups was done by unpaired t-test, while categorical data was analyzed with Chi-square (c2) test. Results: In patients with metabolic syndrome (group I), most of them (68.9%) had more than 2 metabolic components out of 4; the combinations were: high TG + low HDL (54.6%), DM + high TG (46.9%), raised BP + high TG (38.5%), DM + low HDL (33.6%), raised BP + low HDL (26.4%) and raised BP and DM ( 24.3%).ECG shows that the inferior wall acute myocardial infarction (MI) was 41.28% and 44.55% in group I and group II respectively, while anterior wall was involved 58.71 % and 55.65% cases respectively, which was not statistically significant. Heart failure was significantly more in patients of group I than group II (46.79% vs. 20.97%; p<0.001). Echocardiography reveals that the left ventricular (LV) ejection fraction (EF) was much less in group I than that of group II (42.8±18.07% vs. 50.4±21.2%; p<0.001). Among the patients who underwent coronary angiogram (CAG), the mean Friesinger score were 9.7±2.5 in group I and 7.1±3.3 in group II (p<0.05); it indicated more chances of severe coronary artery disease and fatality in group I patients. Conclusion: Acute ST-elevation myocardial infarction patients with metabolic syndrome have much worse angiographic outcome and poor prognosis than those without metabolic syndrome. J Bngladesh Soc Physiol 2021;16(1): 49-56